Medical Student Ophthalmic Knowledge Proficiency after Completing a Clinical Elective or an Online Course - Abou-Hanna, Jacob J.; Yousif, Jonah E.; Kaplan, Ariane D.; Musch, David C.; Trobe, Jonathan D. (Journal of Academic Ophthalmology, 2020)
Background As more information is being packed into medical school curricula, mainstream medical topics legitimately receive more attention than specialty topics such as ophthalmology. However, general practitioners, as gatekeepers of specialty care, must attain competency in ophthalmology. We have investigated whether an online ophthalmology course alone would be noninferior to the same online course plus an in-person clinical elective in providing ophthalmic knowledge.Methods Students at the University of Michigan Medical School voluntarily enrolled in one of two groups: an Online Only group requiring satisfactory completion of an online course entitled “The Eyes Have It” (TEHI) or a Clinical + Online group requiring students to complete a 2-week clinical rotation and the TEHI online course. The outcome metric was the score on an independent 50-question written examination of ophthalmic knowledge. Students also completed a survey assessing confidence in managing ophthalmic problems.Results Twenty students in the Clinical + Online group and 59 students in the Online Only group completed the study. The Clinical + Online group slightly outscored the Online Only group (86.3 vs. 83.0%, p = 0.004). When the two outlier questions were removed from the analysis, there was no difference in mean scores between the two groups (85.8 vs. 85.4, p = 0.069). Students in the Clinical + Online group devoted 80 more hours to the experience than did the students in the Online Only group. The number of hours devoted to the course and interest in ophthalmology were weakly correlated with examination performance. After completion of the experiment, there was no difference in student-reported comfort in dealing with ophthalmic problems between the two groups.Conclusion The examination scores of the students who completed the in-person alone were only slightly inferior to those of the students who completed the in-person clinical elective and the online course. These results suggest that an online course alone may provide a satisfactory ophthalmic knowledge base in a more compact timeframe, an alternative that should have appeal to students who do not intend to pursue a career in ophthalmology.
Keywords: online course; clinical elective; clinical rotation; ophthalmology medical education